Republic of Latvia : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2004)
This report on the Observance of Standards and Codes (ROSC) Data Module provides a review of Latvia's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), complemented by the in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. The assessment reveals that the quality of Latvia's data is generally good. The authorities follow an open dissemination policy, and make freely available a wide variety of data and metadata through official publications, press releases, and on the Internet.